2007
DOI: 10.1007/s11661-007-9324-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Degree of Deformation and Deformation Temperature on Primary Recrystallization Textures in Polycrystalline Nickel

Abstract: The effects of both deformation temperature and degree of deformation on the deformation texture, recrystallization behavior, and recrystallization texture were studied for cold-rolled, high-purity, polycrystalline nickel. Differential scanning calorimetry was used to determine both the stored energy of deformation and the recrystallization temperature, and electron backscatter patterns were employed to reveal both the deformation and recrystallization textures of nickel rolled to either 90 pct thickness reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Figure 5a shows that their fraction decreases from 13 to 4% with increasing number of ARB cycles in the internal layers. Similar decrease was reported with increasing the rolling reduction ratio [5], most probably because of the decreasing grain size. Moreover, it was demonstrated that the fraction of twin decreases drastically with the increasing annealing temperature from 700 to 1000 °C for hot rolled Ni-14Ni alloys [4].…”
Section: Microstructural and Textural Characteristics Through Sample supporting
confidence: 85%
See 1 more Smart Citation
“…Figure 5a shows that their fraction decreases from 13 to 4% with increasing number of ARB cycles in the internal layers. Similar decrease was reported with increasing the rolling reduction ratio [5], most probably because of the decreasing grain size. Moreover, it was demonstrated that the fraction of twin decreases drastically with the increasing annealing temperature from 700 to 1000 °C for hot rolled Ni-14Ni alloys [4].…”
Section: Microstructural and Textural Characteristics Through Sample supporting
confidence: 85%
“…Conventional thermo-mechanical processing (TMP) such as rolling followed by annealing treatment allows an easy development of the {001}〈100〉 Cube texture [1]. However, the volume fraction of this Cube texture strongly depends on the thermo-mechanical processing (TMP) conditions [3,5]. It was demonstrated that by increasing the thickness reduction during cold rolling of pure Ni, the stored energy increased and strengthened both the rolling texture and the recrystallized Cube texture sharpened [5], the rolling temperature had little effect on the {001}〈100〉 Cube texture [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the area closer to the WZ has a lower YS, and consequent higher degree of deformation decreases the recrystallization temperature. [41] In addition, the temperature of WZ is higher, so serious dynamic recrystallization will occur at the WZ. The maximum temperature distribution models in the peripheral and central regions are proposed according to the temperature of the WZ.…”
Section: Discussionmentioning
confidence: 99%
“…The process of annealing results in the formation of strong cube texture ({001}b100N) despite the fact that the cube component shows negligible presence in the deformed structure [4,5]. Various processing parameters including the level of deformation, deformation temperature and annealing temperature can strongly affect the strength and sharpness of cube texture [6,7]. The origin of the cube texture has been explained on the basis of two contrasting theories, namely oriented nucleation (ON) or oriented growth (OG) [8].…”
Section: Introductionmentioning
confidence: 99%